"Anything Can Be Used to Stimulate Child Development": Early Childhood Education and Development in Indonesia as a Durable Assemblage. Issue 1 (30th January 2017) - Newberry, Jan
Abstract : An explosion of early childhood programs in Yogyakarta, Indonesia, has followed on disaster, democratization, growth of the middle class, and global neoliberal reform at the beginning of the twenty-first century. New forms of professional expertise have emerged as a part of this global assemblage to deal with the expanded notions of development advocated by the World Bank and other intergovernmental organizations. Yet, what has remained relatively unremarked is the continued reliance on older New Order forms of social welfare linked to the community form and women's labor. Here, trauma healing programs aimed at the young after the 2006 earthquake, new preschools and playgroups in the era of democratization, and the proliferation of international curricula and pedagogy illustrate how the restless contingency associated with global assemblages is rooted in durable forms of community organization.